Design, Synthesis, and Biological Characterization of Novel Mitochondria Targeted Dichloroacetate-Loaded Compounds with Antileukemic Activity. - Trapella, Claudio; Voltan, Rebecca; Melloni, Elisabetta; Tisato, Veronica; Celeghini, Claudio; Bianco, Sara; Fantinati, Anna; Salvadori, Severo; Guerrini, Remo; Secchiero, Paola; Zauli, Giorgio (J Med Chem, 2015)
The mitochondrial kinase inhibitor dichloroacetate (DCA) has recently received attention in oncology due to its ability to target glycolysis. However, DCA molecule exhibits poor bioavailability and cellular uptake with limited ability to reach its target mitochondria. To overcome these biases, we have synthesized novel DCA-loaded compounds. The selection of the most promising therapeutic molecule was evaluated by combining in vitro assays, to test the antitumoral potential on leukemic cells, and a preliminary characterization of the molecule stability in vivo, in mice. Among the newly synthesized compounds, we have selected the multiple DCA-loaded compound 10, characterized by a tertiary amine scaffold, because it exhibited enhanced (>30-fold) in vitro antitumor activity with respect to DCA and increased in vivo stability. On the basis of these results, we believe that compound 10 should be considered for further preclinical evaluations for the treatment of cancers and/or other diseases characterized by altered metabolic origin.

Kinetic Profiles of Inflammatory Mediators in the Conjunctival Sac Fluid of Patients upon Photorefractive Keratectomy. - Tisato, Veronica; Perri, Paolo; Rimondi, Erika; Melloni, Elisabetta; Lamberti, Giuseppe; Milani, Daniela; Secchiero, Paola; Zauli, Giorgio (Mediators Inflamm, 2015)
Photorefractive keratectomy (PRK) represents a therapeutic option to remodel corneal stroma and to compensate refractive errors, which involves inflammatory and/or regenerative processes. In this context, the modulation of cytokines/chemokines in the conjunctival sac fluid and their role in the maintenance of the corneal microenvironment during the healing process upon refractive procedures has not been deeply investigated. In this study, serial samples of conjunctival sac fluid of patients (n = 25) undergoing PRK were harvested before and at different time points after surgery. The levels of 29 cytokines/chemokines/growth factors involved in inflammatory/immune processes were measured with a multiplex array system. The results have firstly highlighted the different pattern of cytokine expression between the microenvironment at the anterior surface of the eye and the systemic circulation. More importantly, the kinetic of modulation of cytokines/chemokines at the conjunctival level following PRK revealed that while the majority of cytokines/chemokines showed a significant decrease, MCP-1 emerged in light of its pronounced and significant increase soon after PRK and during the follow-up. This methodological approach has highlighted the role of MCP-1 in the healing process following PRK and has shown a potential for the identification of expression/modulation of soluble factors for biomarker profiling in ocular surface diseases.

Serum TRAIL levels increase shortly after insulin therapy and metabolic stabilization in children with type 1 diabetes mellitus. - Tornese, Gianluca; Tisato, Veronica; Monasta, Lorenzo; Vecchi Brumatti, Liza; Zauli, Giorgio; Secchiero, Paola (Acta Diabetol, 2015)

Heterogeneity of mesenchymal stromal cells in lymphoproliferative disorders. - Campioni, Diana; Voltan, Rebecca; Tisato, Veronica; Zauli, Giorgio (Front Biosci (Landmark Ed), 2014)
Accumulating evidence indicates that bone marrow microenvironment plays an important role in the pathogenesis of some myeloid and lymphoid hematological malignancies (HM). Among different environmental associated parameters, those related to functional, cytogenetic and immunological integrity of mesenchymal stromal cells (MSC) are particularly relevant. Functional alterations and immunophenotypic abnormalities have been described in MSC obtained from HM patients. These data seem to confirm the defective biological pattern of MSC especially in myeloid diseases, while MSC cytogenetic profile in HM is still an open question, because it is not clear whether BM stromal cells are "culprit or bystander" displaying or not an abnormal karyotype. Contradictory findings were reported in different HM but the functional implications of altered MSC karyotype need to be further addressed also in light of a clinical use of MSC. A "pathological" in vivo supportive function of endogenous MSC, which provide important survival and drug resistance signals to leukemic cells especially in lymphoproliferative disorders, is suggested. Thus, the mechanisms underlying these protective versus cytotoxic effects exerted by MSC on leukemic cells need further investigations.
Keywords: Humans; Immunophenotyping; Karyotyping; Lymphoproliferative Disorders; Mesenchymal Stromal Cells

In vitro endothelial cell proliferation assay reveals distinct levels of proangiogenic cytokines characterizing sera of healthy subjects and of patients with heart failure. - Voltan, Rebecca; Zauli, Giorgio; Rizzo, Paola; Fucili, Alessandro; Pannella, Micaela; Marci, Roberto; Tisato, Veronica; Ferrari, Roberto; Secchiero, Paola (Mediators Inflamm, 2014)
Although myocardial angiogenesis is thought to play an important role in heart failure (HF), the involvement of circulating proinflammatory and proangiogenic cytokines in the pathogenesis and/or prognosis of HF has not been deeply investigated. By using a highly standardized proliferation assay with human endothelial cells, we first demonstrated that sera from older (mean age 52 ± 7.6 years; n = 46) healthy donors promoted endothelial cell proliferation to a significantly higher extent compared to sera obtained from younger healthy donors (mean age 29 ± 8.6 years; n = 20). The promotion of endothelial cell proliferation was accompanied by high serum levels of several proangiogenic cytokines. When we assessed endothelial cell proliferation in response to HF patients' sera, we observed that a subset of sera (n = 11) promoted cell proliferation to a significantly lesser extent compared to the majority of sera (n = 18). Also, in this case, the difference between the patient groups in the ability to induce endothelial cell proliferation correlated to significant (P < 0.05) differences in serum proangiogenic cytokine levels. Unexpectedly, HF patients associated to the highest endothelial proliferation index showed the worst prognosis as evaluated in terms of subsequent cardiovascular events in the follow-up, suggesting that high levels of circulating proangiogenic cytokines might be related to a worse prognosis.
Keywords: Adult; Cell Proliferation; Cells, Cultured; Chemokines; Cytokines; Heart Failure; Human Umbilical Vein Endothelial Cells; Humans; Middle Aged; Neovascularization, Pathologic; Prognosis

Inverse correlation between circulating levels of TNF-related apoptosis-inducing ligand and 17β-estradiol. - Zauli, Giorgio; Tisato, Veronica; Melloni, Elisabetta; Volpato, Stefano; Cervellati, Carlo; Bonaccorsi, Gloria; Radillo, Oriano; Marci, Roberto; Secchiero, Paola (J Clin Endocrinol Metab, 2014)
CONTEXT: The regulation of the circulating levels of TNF-related apoptosis-inducing ligand (TRAIL), a cytokine of the TNF family, playing a key role in the immune surveillance against cancer, is incompletely understood. OBJECTIVE: The objective of the study was to investigate the potential link between TRAIL and 17β-estradiol. DESIGN, SETTING, AND PARTICIPANTS: Circulating TRAIL levels were measured by an ELISA in plasma samples (n = 246) of healthy, age-matched (range 30-70 y) men and women and in the sera (n = 180) of females belonging to different physiopathological conditions (childhood, pregnancy, under gonadotropin treatment, menopause) characterized by different levels of circulating 17β-estradiol. RESULTS: TRAIL plasma levels in women with aged younger than 50 years were significantly lower compared with age-matched men, whereas in woman 50 years old or older, TRAIL levels were significantly higher compared with the age-matched men and with the younger women. Moreover, an analysis of women with different conditions revealed a significant inverse correlation between the serum levels of TRAIL and 17β-estradiol, with the lowest levels of TRAIL being observed during pregnancy and the highest in childhood and in postmenopausal women. Moreover, gonadotropin treatment in women undergoing assisted reproduction was accompanied by an acute decrease of serum TRAIL levels. Finally, in vitro treatment with 17β-estradiol decreased the TRAIL expression levels in peripheral blood mononuclear cells. CONCLUSIONS: Our data suggest that 17β-estradiol plays a role in regulating TRAIL circulating levels. The demonstration that postmenopausal women exhibit the highest TRAIL levels is of particular interest in light of a previous large study population showing that TRAIL is positively correlated to the overall survival.
Keywords: Adult; Aged; Case-Control Studies; Child; Child, Preschool; Estradiol; Female; Humans; Infant; Male; Middle Aged; Pregnancy; Sex Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

Modulation of circulating cytokine-chemokine profile in patients affected by chronic venous insufficiency undergoing surgical hemodynamic correction. - Tisato, Veronica; Zauli, Giorgio; Gianesini, Sergio; Menegatti, Erica; Brunelli, Laura; Manfredini, Roberto; Zamboni, Paolo; Secchiero, Paola (J Immunol Res, 2014)
The expression of proinflammatory cytokines/chemokines has been reported in in vitro/ex vivo settings of chronic venous insufficiency (CVI), but the identification of circulating mediators that might be associated with altered hemodynamic forces or might represent innovative biomarkers is still missing. In this study, the circulating levels of 31 cytokines/chemokines involved in inflammatory/angiogenic processes were analysed in (i) CVI patients at baseline before surgical hemody namic correction, (ii) healthy subjects, and (iii) CVI patients after surgery. In a subgroup of CVI patients, in whom the baseline levels of cytokines/chemokines were analyzed in paired blood samples obtained from varicose vein and forearm vein, EGF, PDGF, and RANTES were increased at the varicose vein site as compared to the general circulation. Moreover, while at baseline, CVI patients showed increased levels of 14 cytokines/chemokines as compared to healthy subjects, 6 months after surgery, 11 cytokines/chemokines levels were significantly reduced in the treated CVI patients as compared to the CVI patients before surgery. Of note, a patient who exhibited recurrence of the disease 6 months after surgery, showed higher levels of EGF, PDGF, and RANTES compared to nonrecurrent patients, highlighting the potential role of the EGF/PDGF/RANTES triad as sensitive biomarkers in the context of CVI.
Keywords: Adult; Aged; Chemokines; Chronic Disease; Cytokines; Female; Hemodynamics; Humans; Male; Middle Aged; Saphenous Vein; Varicose Veins; Venous Insufficiency

Patients affected by metabolic syndrome show decreased levels of circulating platelet derived growth factor (PDGF)-BB. - Tisato, Veronica; Toffoli, Barbara; Monasta, Lorenzo; Bernardi, Stella; Candido, Riccardo; Zauli, Giorgio; Secchiero, Paola (Clin Nutr, 2013)
BACKGROUND & AIMS: The development and/or progression of metabolic syndrome (MetS) in overweight and obese individuals have been associated to low-grade inflammation, but few studies have simultaneously analyzed the circulating levels of several cytokines. METHODS: In this pilot study, a group of 27 cytokines and growth factors was analyzed in the serum of obese patients (n=40) diagnosed for MetS in comparison with sex- and age-matched control subjects without MetS (n=53) by using a multiplex immunoassay. Release of cytokines was measured in culture supernatants of human primary endothelial cells, THP-1 macrophagic cells and HuH-7 hepatoma cells upon exposure to a high fat mixture. RESULTS: While the majority of cytokines did not show significant differences between the investigated groups, the circulating levels of CXCL10/IP-10 and IL-6 were higher in the MetS group versus overweight control group. In contrast, PDGF-BB serum levels were significantly decreased in MetS patients. The in vitro addition of a high fat mixture increased the release of IL-6 and/or CXCL10/IP-10 in the culture supernatant of human primary endothelial cells and THP-1 macrophagic cells, while the same mixture significantly decreased the release of PDGF-BB by human THP-1 macrophagic and HuH-7 hepatoma cells. CONCLUSIONS: The current demonstration that MetS is associated with decrease of the pro-fibrotic PDGF cytokine is a completely novel finding, which adds complexity to the interplay between inflammation and fibrosis in patients affected by MetS.
Keywords: Adolescent; Adult; Aged; Case-Control Studies; Cell Line, Tumor; Chemokine CXCL10; Endothelial Cells; Female; Humans; Interleukin-6; Linear Models; Male; Metabolic Syndrome X; Middle Aged; Obesity; Pilot Projects; Proto-Oncogene Proteins c-sis; RNA, Messenger; Young Adult

Endothelial cells obtained from patients affected by chronic venous disease exhibit a pro-inflammatory phenotype. - Tisato, Veronica; Zauli, Giorgio; Voltan, Rebecca; Gianesini, Sergio; di Iasio, Maria Grazia; Volpi, Ilaria; Fiorentini, Guido; Zamboni, Paolo; Secchiero, Paola (PLoS One, 2012)
BACKGROUND: The inflammatory properties of vein endothelium in relation to chronic venous disease (CVD) have been poorly investigated. Therefore, new insights on the characteristics of large vein endothelium would increase our knowledge of large vessel physiopathology. METHODOLOGY/PRINCIPAL FINDINGS: Surgical specimens of veins were obtained from the tertiary venous network (R3) and/or saphenous vein (SF) of patients affected by CVD and from control individuals. Highly purified venous endothelial cell (VEC) cultures obtained from CVD patients were characterized for morphological, phenotypic and functional properties compared to control VEC. An increase of CD31/PECAM-1, CD146 and ICAM-1 surface levels was documented at flow cytometry in pathological VEC with respect to normal controls. Of note, the strongest expression of these pro-inflammatory markers was observed in VEC obtained from patients with more advanced disease. Similarly, spontaneous cell proliferation and resistance to starvation was higher in pathological than in normal VEC, while the migratory response of VEC showed an opposite trend, being significantly lower in VEC obtained from pathological specimens. In addition, in keeping with a higher baseline transcriptional activity of NF-kB, the release of the pro-inflammatory cytokines osteoprotegerin (OPG) and vascular endothelial growth factor (VEGF) was higher in pathological VEC cultures with respect to control VEC. Interestingly, there was a systemic correlation to these in vitro data, as demonstrated by higher serum OPG and VEGF levels in CVD patients with respect to normal healthy controls. CONCLUSION/SIGNIFICANCE: Taken together, these data indicate that large vein endothelial cells obtained from CVD patients exhibit a pro-inflammatory phenotype, which might significantly contribute to systemic inflammation in CVD patients.
Keywords: Adult; Antigens, CD146; Antigens, CD31; Body Mass Index; Cell Culture Techniques; Endothelial Cells; Female; Flow Cytometry; Humans; Inflammation; Intercellular Adhesion Molecule-1; Kinetics; Male; Microscopy, Electron, Scanning; Middle Aged; Phenotype; Saphenous Vein; Vascular Diseases

The energy balance positively regulates the levels of circulating TNF-related apoptosis inducing ligand in humans. - Biolo, Gianni; Secchiero, Paola; De Giorgi, Sara; Tisato, Veronica; Zauli, Giorgio (Clin Nutr, 2012)
BACKGROUND & AIMS: Although decreased levels of circulating TRAIL have been associated to cardiovascular risk and overall mortality, the mechanisms controlling TRAIL levels in physiopathological conditions are currently unknown. The aim of the present study was to investigate whether changes in the energy intake and insulin sensitivity may influence circulating TRAIL, and to analyze potential relationships between circulating TRAIL and changes in fat mass in healthy subjects receiving hypocaloric or hypercaloric diets. METHODS: Three distinct groups of participants were studied, at the end of a 14-day (n = 9), 35-day (n = 30) or 60-day (n = 16) period of experimental bed rest to induce insulin resistance and during controlled ambulation, after receiving eucaloric, hypocaloric or hypercaloric diets. RESULTS: After bed rest conditions, energy restriction significantly decreased circulating TRAIL, while overfeeding significantly increased TRAIL levels with respect to eucaloric control subjects. Moreover, a positive correlation was found between levels of circulating TRAIL and energy intake as well as between circulating TRAIL and energy balance, as determined by changes in fat mass in these subjects. CONCLUSIONS: Circulating levels of TRAIL exhibit a clear-cut positive correlation with the energy intake and balance in healthy subjects during experimental physical inactivity.
Keywords: Adult; Apoptosis; Bed Rest; Cross-Over Studies; Diet; Energy Intake; Energy Metabolism; Female; Humans; Insulin Resistance; Male; Motor Activity; Risk Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

Simultaneous determination of multiple cytokines reveals a pro-inflammatory and pro-angiogenic signature after major cardiothoracic surgery: potential role of C-reactive protein. - Tisato, Veronica; Monasta, Lorenzo; Biolo, Gianni; Donatelli, Francesco; Secchiero, Paola; Zauli, Giorgio (Cytokine, 2012)
Keywords: C-Reactive Protein; Coronary Artery Bypass; Cytokines; Humans; Inflammation; Macrophages; Neovascularization, Physiologic; Risk Factors

Soluble TRAIL is elevated in recurrent miscarriage and inhibits the in vitro adhesion and migration of HTR8 trophoblastic cells. - Agostinis, Chiara; Bulla, Roberta; Tisato, Veronica; De Seta, Francesco; Alberico, Salvatore; Secchiero, Paola; Zauli, Giorgio (Hum Reprod, 2012)
STUDY QUESTION: What is the potential physiopathological role of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) in recurrent miscarriage (RM), characterized by at least three consecutive pregnancy losses. SUMMARY ANSWER: The levels of serum TRAIL immediately after miscarriage in RM patients are significantly elevated with respect to that in first-trimester normal pregnant women, and recombinant TRAIL inhibits the adhesion and migration of HTR8 trophoblastic cells in vitro. WHAT IS KNOWN ALREADY: Both TRAIL and its trans-membrane receptors (TRAIL-R1, TRAIL-R2, TRAIL-R3 and TRAIL-R4) have been documented in the placenta, but their physiopathological role is incompletely understood. STUDY DESIGN, SIZE, DURATION: The study populations consisted of RM patients (n = 80) and first-trimester normal pregnant women (n = 80). Blood samples were obtained within 24 h after abortion (RM) or at gestational 12-week (normal pregnant women). As additional controls, third-trimester normal pregnant women (n = 28) were examined before (within 72 h) and after (within 24 h) partum. PARTICIPANTS/MATERIALS, SETTING, METHODS: The concentrations of TRAIL were analysed in serum samples by ELISA. In parallel, the effect of soluble recombinant TRAIL (0.1-1000 ng/ml) was analysed on the survival of primary extravillus trophoblasts (EVTs) and on the survival, proliferation, adhesion and migration of trophoblastic HTR8 cells. MAIN RESULTS AND THE ROLE OF CHANCE: The circulating levels of TRAIL in RM women (median: 52.5 pg/ml; mean and SD: 55.5 ± 24.4 pg/ml) were significantly higher with respect to first-trimester normal pregnant women (median: 44.9 pg/ml; mean and SD: 47 ± 15.1 pg/ml) and third-trimester normal pregnant women, as assessed before (median: 45.1 pg/ml; mean and SD: 46 ± 12.4 pg/ml) and after partum (median: 35.4 pg/ml; mean and SD: 38 + 17.5 pg/ml). Both primary EVT and HTR8 cells expressed detectable levels of TRAIL death receptors, but exposure to soluble recombinant TRAIL did not induce cell death of trophoblastic cells. On the other hand, TRAIL dose-dependently inhibited the adhesion of HTR8 cells to decidual endothelial cells (DEC) as well as the migration of HTR8 in transwell assays using either fibronectin or DEC. LIMITATIONS, REASONS FOR CAUTION: Although this study suggests that TRAIL might have a pathogenic role in RM by inhibiting both the adhesion and migration capabilities of first trimester trophoblastic cells, there is a possibility that the elevated serum levels of TRAIL in RM are not cause but rather the result of RM. WIDER IMPLICATIONS OF THE FINDINGS: Our current findings together with data of other authors suggest that circulating TRAIL should be further analysed as a potential important biomarker in different physiopathological settings. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by FIRB projects (RBAP11Z4Z9_002 to Giorgio Zauli and RBAP10447J_002 to Paola Secchiero). The authors have no competing interests to declare.
Keywords: Abortion, Habitual; Apoptosis; Cell Adhesion; Cell Line; Cell Movement; Cells, Cultured; Enzyme-Linked Immunosorbent Assay; Female; Humans; Pregnancy; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand; Trophoblasts